Film tourism in Poland: potential and perspectives for development - Stasiak, Andrzej (Bulletin of Geography. Socio-economic Series, 2022)
Travel has been inspired by films for many years, but only in the early 21st century did it begin to constitute a significant volume. In many places in the world, film tourism has become a true phenomenon. The paper constitutes the first so broad an attempt at determining the state of film tourism in Poland. Based on 15 years of the author’s own research and research by other Polish scholars, an inventory of film heritage (film locations, museums, festivals and other attractions) was taken and – as far as the available data allowed – the characteristics of associated tourist traffic were provided. The research procedure revealed numerous gaps in our knowledge. Hence, apart from other conclusions, a list of problems that, in the years to come, should become a subject of interest among cultural tourism scholars in Poland was included in the summary.